Interactions between temperament and expectations of classmates as predictors of social support amongst lower secondary school girls - Teoh Hsien -Jin (penerbit ukm, 2004)
One hundred thirty six lower secondary school girls were interviewed to find out how interactions between their temperaments, and what their classmate’s expected of their general behaviours, generally predicted social support levels. An important part of this study is the testing of the ‘Goodness-of-Fit’ model. Results indicated that the better the fit between classmate’s demands and the student’s temperament, in terms of mood and distractibility, the more social support they tended to have in class. Implications of the results would indicate that paying attention to schoolwork tasks, and having a positive disposition is important for getting social support from classmates.